2004
DOI: 10.1002/ajmg.a.30004
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic disorders in Prader–Willi syndrome

Abstract: The Prader-Willi syndrome (PWS) is a genetically determined developmental disorder caused by abnormalities of the proximal region of chromosome 15q11-13. In a previous study, we reported that psychotic episodes, occurring in 16% of persons with PWS, had an onset in adolescence, never occurred in persons with paternal deletion, and were exclusively associated with maternal uniparental disomy (UPD) or imprinting abnormalities (IM). In order to gain a better understanding of the psychopathology and to further ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 32 publications
3
61
1
Order By: Relevance
“…21 Psychosis is evident by young adulthood in at least 5 -10% of the individuals. 17,22,23 Other characteristics A number of less consistent features are nonetheless common and/or characteristic, and may be important for diagnosis or management (Figures 2 -3 30,31 found that obesity-related cardiovascular and respiratory disorders were the most frequent causes of death in both children and adults. Based on a population study, the death rate has been estimated at 3% per year.…”
Section: Short Staturementioning
confidence: 99%
See 1 more Smart Citation
“…21 Psychosis is evident by young adulthood in at least 5 -10% of the individuals. 17,22,23 Other characteristics A number of less consistent features are nonetheless common and/or characteristic, and may be important for diagnosis or management (Figures 2 -3 30,31 found that obesity-related cardiovascular and respiratory disorders were the most frequent causes of death in both children and adults. Based on a population study, the death rate has been estimated at 3% per year.…”
Section: Short Staturementioning
confidence: 99%
“…It is particularly important to be aware that psychosis develops in a substantial number of adults with UPD or imprinting defects. 22,23 Psychosis is treated in a standard manner.…”
Section: Developmental Disabilitymentioning
confidence: 99%
“…[19][20][21] In the general population, psychotic illnesses result in a substantially increased risk of death at a relatively young age. Overall, people with schizophrenia have a two-to threefold increased risk of premature dying.…”
Section: Psychiatrymentioning
confidence: 99%
“…PWS is characterized by a specific behaviour profile comprising obsessions/compulsions, inflexibility and temper tantrums [28, 29], in addition to a mild intellectual disability with a mean IQ of 60 points [30, 31]. Moreover, psychotic episodes occur in about 20% of young adults and are more frequent in patients with maternal uniparental disomy (UPD) [32, 33]. Adolescence is a critical period in PWS due to an increase in disruptive or antisocial behaviour and in emotional disturbances [34].…”
Section: Introductionmentioning
confidence: 99%